Strategi Pengemasan dan Pemasaran Produk Lomang Panas Jaya Tanjung Selamat Medan - Marbun, Patar (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
SMEs are the driving force of the economy in communities with limited economies. The most common SME business sector is the culinary sector. People from various circles can run this business field. The products that can be offered are very diverse, and can also be adapted to each person's abilities. One of the potentials that can be developed is the UMKM (Micro, Small and Medium Enterprises) industrial sector. One of the SMEs on a home industry scale which operates in the food business sector is the Lomang Panas Jaya Business which is located on Jalan Flamboyan Raya No. 5, Tanjung Selamat-Medan, Tanjung Selamat Village. The existence of this business attracts the attention of local residents, because the specialty of the food products offered is food that is always hot but is still in great demand by the public. However, the problem is the lack of understanding about good product packaging, the lack of a brand name or brand and systematic marketing activities. This is a common problem for development. The result of this problem is that it is difficult to reach new customers. The activity plan is designed to be able to answer and find solutions to these problems. Assistance from implementation to evaluation is carried out by first carrying out a situation analysis to truly understand the conditions and potential of the Lomang Panas Jaya Business. The output target of this community service activity is increasing knowledge of good and attractive packaging, strategic marketing plans and sustainable business plans.